Cloud-based Learning Environments: Investigating Learning Activities Experiences from Motivation, Usability and Emotional Perspective - Rizzardini, R.; Amado-Salvatierra, H.; Guetl, Christian (SCITEPRESS, 2013)
Cloud education environments consider all the cloud services, such as Web 2.0 applications, content, or infrastructure services. These services form an e-learning ecosystem which can be built upon the learning objectives and the preferences of the learner group. A great variety of existing cloud services might be repurposed for educational activities and it can be taken advantage from already widely used services without steep learning curves on their adoption. In this article is presented the design, deployment and evaluation of learning activities using cloud applications and services. The experiences presented here are from Galileo University in Guatemala with students from three different countries in Central America and Spain. This study reports findings from motivational attitudes, emotional aspects and usability perception. Selected cloud-based tools were used for the different learning activities in three courses in various application domains. These activities include collaboration, knowledge representation, storytelling activities and social networking. Experimentation results obtained aim to demonstrate that students are eager to use and have new and more interactive ways of learning, which challenges their creativity and group organization skills, while professors have a growing interest on using new tools and resources that are easy to use, mix and reuse. Thus, future research should focus on incentives for motivating participation as well as on providing systems with high usability, accessibility and interoperability that are capable of doing learning orchestration.